Social Capital and its implication on Health Promotion among rural Primary Schools in Botswana - Chepete, Koziba (Graduate School of Business (GSB), 2023)
The World Health Organization (WHO) estimates 1.7 million child and adolescent deaths in 2016. These deaths were due to road injuries, diarrhoeal diseases, consequences of non-communicable diseases and environmental hazards. Whilst most of these deaths are deemed preventable through school health promotion programs, there are challenges with availability of healthcare professionals and resources for health promotion, particularly in rural settings. WHO further estimates a 1.1 million global shortage of healthcare professionals by 2030, further limiting the availability of human resources for school health promotion programs. This study therefore analysed the implications of social capital in health promotion among rural primary schools. The objective was to examine the evidence for what is possible and likely to work in rural social and health capital investment. A qualitative approach, through semi-structured interviews, wasselected to study the beliefs and practices of teachers regarding health promotion. This study found that parental negligence, poor hygiene and lack of in-service and post-service training of teachersin health-related matters were among the major health promotion challenges in a rural district of Botswana. Strengthening social capital could yield positive results in improving inclusive and sustainable health promotion strategies in rural primary schools, where there is a burden of need.